ANALISIS KEMAMPUAN LITERASI MATEMATIKA PADA GAYA KOGNITIF DI ERA IMPLEMENTASI MERDEKA BELAJAR - Karmilatun Rasyidah; Husnul Khatimah (Yayasan Nusantara Hasana Berdikari, 2024)
Mathematical literacy ability is an ability possessed by individuals, not only conceptual, but can understand problem solving procedures, know facts and can also apply knowledge of mathematical concepts and problems. The purpose of this study was to describe the level or level of mathematical literacy skills in SMP Islam Terpadu Rabbani Quran School Blangidie in the Field Dependent and Field Independent cognitive styles. This type of research is descriptive research (qualitative). The research method used in this study is a case study. This study took 4 subjects from each cognitive style category. The data collection technique used was the GEFT test, math literacy test questions, interviews, documentation and triangulation and data analysis used in this study, namely editing, classification, verification, analysis and drawing conclusions.The findings of this research indicate that each category of cognitive style, Field Dependent and Field Independent, differs. Subjects classified as Field Dependent exhibit mathematical literacy skills that have not yet met all indicators and are unable to solve all problems correctly, only managing to solve problems 2 and 4. Meanwhile, subjects classified as Field Independent possess mathematical literacy skills that also enable them to solve only problem 2 correctly through all stages and problem 4 with some difficulty in the resolution stage.